(untitled) (Indo-MathEdu Intellectuals Journal, 2025)
Entering the era of globalization and the industrial revolution 4.0, the world of work is experiencing very dynamic, complex, and competitive changes. These changes require the younger generation, especially final year students such as at the State Islamic Senior High School (MAN), to be ready to plan their future careers carefully. The purpose of this study was to determine whether there is an influence of self-efficacy on career maturity. This study uses an inferential quantitative approach. The population in this study were students of MAN Y in Makassar City. This study used the Accidental Sampling technique with a sample size of 45 MAN students in Makassar. The instruments in this study were the career maturity scale and the self-efficacy scale in the form of a Likert Scale. The data analysis used was simple regression analysis. The results of the study showed a Significance value (Sig.) = 0.001, which is much smaller than 0.05 (the level of significance commonly used). This means that the regression model is statistically significant, namely self-efficacy has a significant effect on career maturity. The conclusion of this study is that self-efficacy plays a significant role in the career maturity of MAN Y students in Makassar City. The implications of this study for schools and guidance and counseling teachers at MAN to improve student self-efficacy can be one of the strategic interventions in order to develop student career maturity.